2022
DOI: 10.3390/ijerph191912109
|View full text |Cite
|
Sign up to set email alerts
|

Does Cycling Training Reduce Quality of Functional Movement Motor Patterns and Dynamic Postural Control in Adolescent Cyclists? A Pilot Study

Abstract: The aim of this study was to assess whether cycling training may influence quality of functional movement patterns and dynamic postural control. We also sought to determine if the Functional Movement Screen and Lower Quarter Y-balance tests could be predictive of injury risk among adolescent road cyclists. Twenty-three male road cyclists, aged 15–18 years, were involved in the study. Quality of functional movement patterns was assessed using the Functional Movement Screen test (FMS). Dynamic postural control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…According to De Noronha et al 14 , normalised posterolateral (PL) reaches <80% have been linked to increased risk of ankle sprains. However, there are also studies in which no association would be shown between YBT-LQ performance and risk of injury among athletes [15][16][17][18][19][20] . The findings of Lisman et al 20 allow to suggest that YBT-LQ is not connected with increased risk of lower limb injury in high-school athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to De Noronha et al 14 , normalised posterolateral (PL) reaches <80% have been linked to increased risk of ankle sprains. However, there are also studies in which no association would be shown between YBT-LQ performance and risk of injury among athletes [15][16][17][18][19][20] . The findings of Lisman et al 20 allow to suggest that YBT-LQ is not connected with increased risk of lower limb injury in high-school athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lai et al 15 and Wright et al 16 also demonstrated that no reach asymmetry nor composite score can predict lower limb injury in collegiate athletes. Moreover, in some studies, it has been indicated the YBT-LQ to be a poor injury-predictive tool in specific sports populations such as American football 17 and basketball players 18 , or adolescent road cyclists 19 . Plisky et al 21 suggested that the reason of inter-population differences in YBT-LQ's predictive validity may be the lack of cut-off value adjustment.…”
Section: Introductionmentioning
confidence: 99%